Age-related differences and vascular function test findings in patients with vasospastic angina. (25th November 2020) - Kato, K; Tateishi, K; Saito, Y; Kitahara, H; Fujimoto, Y; Kobayashi, Y
Abstract: Background: Vasospastic angina (VSA) accounts for the majority of angina cases with no epicardial stenosis and develops amongawide range of age, which is reportedly induced by coronary functional abnormalities including endothelial dysfunction and smooth muscle hypercontraction. However, the relation of noninvasive vascular function tests to VSA remains to be fully elucidated. Purpose: The aim of this study was to assess differences in clinical characteristics and findings from noninvasive vascular function tests among groups by age in patients with VSA. Methods: We enrolled a total of 732 patients with angina who underwent intracoronary acetylcholine provocation test. VSA was defined as total or subtotal occlusion of epicardial coronary arteries accompanied by chest pain and/or ischemic electrocardiographic changes in response to acetylcholine administration. Patients with VSA were divided into 3 groups by age (young [<50 years], intermediate [50–64 years], and elderly group [≥65 years]). Noninvasive vascular function test findings such as ankle-brachial index (ABI), brachial-ankle pulse wave velocity (baPWV), andpercentage of mean arterial pressure (%MAP) were compared among groups by age in patients with VSA. Results: Of all patients, 367 (50.1%) were diagnosed as VSA with intracoronary acetylcholine test, including 66 (18.0%), 113 (30.8%), and 188 (51.2%) patients in the young, intermediate, and elderly groups. Among groups by age, there was no significant difference in gender (female, 31.8% vs. 40.7% vs. 44.7%, P=0.19). Patients in the young group were more often smokers and alcohol drinkers than those in the intermediate and elderly groups, while the prevalence of hypertension, dyslipidemia, and diabetes were lower in younger patients. A history of percutaneous coronary intervention was less frequently found in the young group compared tothe intermediate and elderly groups (7.6% vs. 16.8% vs. 20.7%, P=0.033). The baPWV was higher in the elderly group (1424±232 vs. 1537±247 vs. 1774±358 cm/s, P<0.0001), while there was no difference in ABI between the 3 groups. %MAP at arms was significantly and progressively decreased with an increase in age (54.0±4.5% vs. 53.0±2.6% vs. 51.2±2.8%, P<0.0001). Conclusion: Our study demonstrated that there were distinct age-related differences in clinical characteristics of patients with VSA. The higher %MAP in younger patients suggests that more impaired endothelial dysfunction may play a role in the development of VSA in this age group. Funding Acknowledgement: Type of funding source: None